Um conúbio intrigante na construção de um herói romântico: os caminhos da produção das Mémoires de Garibaldi (1860), de Alexandre Dumas - Nogueira, Isabella (2018)
This dissertation aims to investigate the production of the book Mémoires de Garibaldi, published in Paris by Alexandre Dumas, in 1860. According to the writer, after having had access to Garibaldi's manuscript, his objective was to comment and publish such pages. Working with the hypothesis that Dumas was more present in the book than he actually said and Dumas saw in the character the romantic hero. So it was been decided to develop the problematic of production in two chapters. The first one presents the relation between the two personages and in him it is perceived that Dumas went in search of Garibaldi with the interest to publish his memories after a financial crisis passed by the literate and the repercussion of the done of the general. In spite of this, he saw in Garibaldi one man above the others, which led him to want to be with him for four years. Garibaldi was already a character known and exalted for his heroic deeds, but it was the writer who gave him more visibility. In the second chapter, it was been tried to think the problematic of the production between the textuality and the materiality of the work, presenting what is written and its scenery. Still, it came to be observed that the memories of 1860 approach the narrative techniques of Dumas. This was possible through the study of Garibaldi's memoirs published in 1859 in New York by Theodore Dwight and the 1888 edition published by Bàrbera. Despite the similarity between these editions and that of Dumas, with their differences, the one had more repercussion. We will notice that there have been many translations and re-editions.